Integration of Islamic Values ​​in Competency-Based Curriculum: (Case Study of Kindergarten Al Iman Jombang) - Farikhah, Iftitakhul; Suwignya, Miftahul Ilmi; Ulwiyah, Nur (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2024)
This research examines the implementation of a competency-based curriculum that is integrated with Islamic values at the Early Childhood Education (ECE) level, especially at Al Iman Kindergarten in Jombang. (ECEP), especially at Al Iman Kindergarten in Jombang. Islamic values, such as obedience to worship, honesty and responsibility, are integrated through experiential learning and habituation approaches. experiential learning and habituation approaches. The research uses a qualitative method with a case study approach, involving observation, in-depth interviews, and curriculum document analysis. The result of the research showed that the integration of Islamic values not only serves as a moral foundation, but also supports the formation of character, intelligence and moral foundation, but also supports the formation of children's character, intelligence, emotional emotional intelligence, and children's skills in facing the demands of globalization. The curriculum at Al Iman Kindergarten is designed to create active and relevant learning, with the vision of building a human being who is relevant, with the vision of building Islamic, creative, and integrity people. The implementation strategy involves habituation methods, integration of Islamic values in daily activities, and values in daily activities, and the support of all stakeholders. This research contributes to the development of ECEP curriculum curriculum development based on Islamic values as a holistic education model that supports children's children's growth in spiritual, intellectual, and moral aspects.